Development of a novel green adsorbent for the removal of chloroethene compounds from contaminated water / Geetha Selvaraju - Geetha , Selvaraju (2018)
In this study, a novel green activated carbon adsorbent was developed from an agrofood- waste abundantly available in Malaysia (Artocarpus integer fruit processing waste) by steam activation. Proximate, elemental and component analyses showed that the raw bio-waste material is rich in cellulose (53.6 wt%), carbon (60.8 wt%) and volatile inorganic matter, making it a good choice of green-adsorbent material. The adsorbent preparation conditions were optimised and the optimal adsorbent was characterised by several techniques. The results revealed that pyrolysis at 700°C for 60 min and steam activation at 750°C for 60 min were appropriate to attain a high quality adsorbent with a large iodine adsorption capacity (1411 mg/g), reasonable yield (31.30%), highly micro-mesoporous (Brunauer-Emmett-Teller (BET) surface area ~853 m2/g, t-plot micropore surface area ~506 m2/g, t-plot mesopore surface area ~346 m2/g and average pore width 2.9 nm) and amorphous structure with predominantly basic surface functional groups with pHpzc 8.3, which are all advantageous properties for adsorption applications. The adsorbent was evaluated for the removal of carcinogenic chloroethenes, namely tetrachloroethene (PCE), trichloroethene (TCE), cisdichloroethene (cis-DCE), trans- dichloroethene (trans-DCE) and vinyl chloride (VC) from contaminated water. The effects of adsorbent dosage, temperature, pH, initial concentration of chloroethenes and contact time on removal of chloroethene compounds were examined by GC-ECD. The maximum removal of PCE, TCE, cis-DCE, trans- DCE and VC from spiked aqueous solutions was obtained at pH 8 as 87%, 85%, 82%, 82% and 81% respectively for adsorbent dose of 5 g/L and 50 mg/L initial chloroethene concentration at 40°C with agitation for 15 min. EDX spectra revealed the presence of chlorine peak and elemental mapping analysis showed a high distribution of chlorine in the adsorbent after sorption experiments, proving that the adsorbent is capable of effectively extracting chloroethene compounds from contaminated water. The developed method showed satisfactory reproducibility (RSD <6.5%), linearity (r > 0.9887), detection limits for chloroethenes (0.93-1.54 μg/L) and quantification limits for chloroethenes (2.35-3.10 μg/L). The proposed method also exhibited a high degree of inter- and intra-day accuracy under the optimum experimental conditions. The practical applicability of the novel adsorbent was studied via the removal of chloroethene compounds from domestic wastewater samples. The maximum removal of PCE, TCE, cis-DCE, trans-DCE and VC from domestic wastewater was obtained as 79%, 77%, 75%, 75% and 72% respectively for 50 mg/L initial chloroethene concentration, under the optimised conditions. The performance of the produced adsorbent was evaluated against a commercial coal-based activated carbon. The newly developed adsorbent was shown to be a promising alternative to commercial coal-activated carbon which may be used as a cleaner and ecologically compatible adsorbent for the removal of chloroethene compounds from contaminated water.